2001
DOI: 10.1111/j.0014-3820.2001.tb00762.x
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization Selection on Egg and Jelly-Coat Size in the Sand Dollar Dendraster Excentricus

Abstract: Abstract. Organisms with external fertilization are often sperm limited, and in echinoids, larger eggs have a higher probability of fertilization than smaller eggs. This difference is thought to be a result of the more frequent spermegg collisions experienced by larger targets. Here we report how two components of egg target size, the egg cell and jelly coat, contributed to fertilization success in a selection experiment. We used a cross-sectional analysis of correlated characters to estimate the selection gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…In similar experimental designs to the present study, both Podolsky (2001) and Levitan and Irvine (2001) showed that an increase in the jelly coat area of echinoderm eggs is selected for in sperm-limiting conditions. However, Podolsky (2001) argued that as selection pressures were similar for both the ovicell and jelly coat, and jelly coats are cheaper to produce, selection should favour increased investment in jelly coats.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In similar experimental designs to the present study, both Podolsky (2001) and Levitan and Irvine (2001) showed that an increase in the jelly coat area of echinoderm eggs is selected for in sperm-limiting conditions. However, Podolsky (2001) argued that as selection pressures were similar for both the ovicell and jelly coat, and jelly coats are cheaper to produce, selection should favour increased investment in jelly coats.…”
Section: Discussionsupporting
confidence: 65%
“…However, Podolsky (2001) argued that as selection pressures were similar for both the ovicell and jelly coat, and jelly coats are cheaper to produce, selection should favour increased investment in jelly coats. In contrast, Levitan and Irvine (2001) argued that because the unstandardized selection gradient was much steeper for the ovicell, selection should favour increased investment in the ovicell. In our study, we found no selection for ovicell size in sperm-limiting conditions, but instead found that more eggs with smaller ovicells were successfully fertilized in high sperm concentrations.…”
Section: Discussionmentioning
confidence: 97%
“…Subsequent studies supported the assertion that physical size of the egg cell influenced fertilization success (e.g. Levitan and Irvine 2001) , whereas others-sometimes working on the very same species-argued for an equally important role of egg accessory structures such as egg jelly or follicle cells (e.g. Podolsky 2001) .…”
Section: In Broadcast Spawnersmentioning
confidence: 92%
“…Rothschild and Swann (1951) , Vogel et al (1982) , Destombe et al (1990), Levitan et al (1991) , Levitan (1993Levitan ( , 2000 , Manríquez et al (2001) , Powell et al (2001), Kupriyanova and Havenhand (2002) , Johnson and Yund (2004) , Levitan et al (2004) , Hodgson et al (2007), Muhlin et al (2008 Size Podolsky (2004) Egg Accessory structures (jelly coat, follicle cells, etc.) Lambert and Lambert (1981), Buckland-Nicks (1993), Farley andLevitan (2001), Levitan and Irvine (2001) , Podolsky (2001Podolsky ( , 2002Podolsky ( , 2004 , Villa and Patricolo (2001) Chemotaxis, chemokinesis Miller (1975Miller ( , 1985 , Maier and Müller (1986 , review), Bolton and Havenhand (1996) , Serrão et al (1996a...…”
Section: Main Topics In Fertilization Ecology Of Rocky Shore Speciesmentioning
confidence: 99%
“…Additionally, the preference of a sperm for certain eggs within a single species (Evans et al, 2012), and viability of both the egg and sperm (Giorgi and DeMartini, 1977) can decrease actual and predicted fertilization rates. In the absence of flow, the effective target size of the egg increases fertilization rates and decreases the negative impact of sperm limitation and sperm dilution (Farley, 2002;Farley and Levitan, 2001;Jantzen et al, 2001;Levitan, 1993Levitan, , 1996Levitan, , 2000Levitan, , 2006Levitan and Irvine, 2001;Styan, 1998).…”
Section: Introductionmentioning
confidence: 99%